2020
DOI: 10.1177/0271121420942308
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Parent and Teacher Questionnaires to Screen for Language Disorders in Bilingual Children

Abstract: We explore the classification accuracy of a parent and teacher report measure, the Inventory to Assess Language Knowledge (ITALK), to screen for developmental language disorder (DLD) in bilingual children. Participants included 120 Spanish English bilingual children with typical development (TD) and 19 bilingual children with DLD, ranging in age from 5 to 8 years old. Parents’ and teachers’ reports correlated moderately with each other and significantly predicted children’s performance on language-specific mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…In their comprehensive review, Pratt et al (2020) examined available questionnaires used to screen for language disorders in bilingual learners. Their review included a variety of tools: Ages and Stages Questionnaire-Spanish ([Spanish ASQ], Squires et al 1999) Pua et al 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…In their comprehensive review, Pratt et al (2020) examined available questionnaires used to screen for language disorders in bilingual learners. Their review included a variety of tools: Ages and Stages Questionnaire-Spanish ([Spanish ASQ], Squires et al 1999) Pua et al 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The Spanish ASQ, INV-II, ALDeQ, and PRSLP engage parents as reporters of children's information, whereas the BLAB utilizes both parents and educators. Overall, Pratt et al (2020) concluded that these instruments lacked the sensitivity required to identify bilingual learners with language disorders. If an instrument cannot clearly measure the constructs or identify a language disorder, then the validity is in question as it does not serve the intended purpose and, thus, impacts accurate assessment.…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations